2021
DOI: 10.1177/23780231211031690
|View full text |Cite
|
Sign up to set email alerts
|

Disenfranchised: How Lower Income Mothers Navigated the Social Safety Net during the COVID-19 Pandemic

Abstract: Government programs and other forms of assistance act as critical safety nets in times of crisis. The federal government’s initial response to coronavirus disease 2019 represented a significant increase in the welfare state, but the provisions enacted were not permanent and did not reach all families. Drawing on interviews with 54 lower-income mothers and grandmothers, we analyze how families navigated the safety net to access food during the pandemic. Pandemic aid served as a critical support for many familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 69 publications
1
26
0
1
Order By: Relevance
“…While stimulus payments such as the CARES (Coronavirus Aid, Relief, and Economic Security) Act and the CRB (Canadian Recovery Benefit) have provided some support to help offset pandemic‐related economic pressures, limitations to policy application (e.g., the exclusion of benefits for dependent children over the age of 16; barriers to access for those with disabilities) limit utility for many families (Marr et al, 2020 ; Saba, 2021 ), plausibly exacerbating levels of parenting stress. Moreover, in the case of working mothers in particular, COVID‐related federal relief around issues such as food insecurity, have been shown to be especially insufficient and/or inaccessible (Elliott et al, 2021 ). That sole mothers are significantly more likely to be food insecure (e.g., Martin & Lippert, 2012 ), suggests the disproportionate harm generated by such policy‐based shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…While stimulus payments such as the CARES (Coronavirus Aid, Relief, and Economic Security) Act and the CRB (Canadian Recovery Benefit) have provided some support to help offset pandemic‐related economic pressures, limitations to policy application (e.g., the exclusion of benefits for dependent children over the age of 16; barriers to access for those with disabilities) limit utility for many families (Marr et al, 2020 ; Saba, 2021 ), plausibly exacerbating levels of parenting stress. Moreover, in the case of working mothers in particular, COVID‐related federal relief around issues such as food insecurity, have been shown to be especially insufficient and/or inaccessible (Elliott et al, 2021 ). That sole mothers are significantly more likely to be food insecure (e.g., Martin & Lippert, 2012 ), suggests the disproportionate harm generated by such policy‐based shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research conducted during COVID-19 suggests that many successful connections to food and material-related resources were given in the context of individual casework, which required “close and trusting relationships” ( Dempsey & Pautz, 2021, p. 17 ). However, some mothers from disenfranchised communities felt that caseworkers conducted meetings as interrogations and failed to provide clear explanations when applications for benefits were denied, which resulted in further mental strains on low-income families ( Elliott et al, 2021 ). These studies underscore the importance of relationships between caseworkers and community members during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, WIC participants also described various forms of what Elliot et. al have described as disenfranchisement (i.e., structures that keep people from seeking public resources [25]) such as experiencing delays in receiving their WIC benefits due to staff shortages in rural areas, being afraid or hesitant to access benefits due to the risk of contracting COVID-19 or unpleasant interactions with WIC staff, and lacking access to fruits and vegetables or other foods in their communities. Additionally, we found that changes in the CVB amount over the period of June to December 2021, including a one-month temporary decrease in benefits, created a notable amount of confusion and uncertainty about redeeming CVB among North Carolina participants.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of fruits and vegetables, especially nutrient-dense varieties, is often lower among children living in rural households and households with low incomes and children from historically marginalized racial or ethnic groups [10][11][12][13][14][15][16]. Across the US, structural factors such as high cost and disparate physical access to fruits and vegetables as well as divestment in communities make it more challenging for children living in rural areas, in households with low incomes, and from historically marginalized racial/ethnic groups to meet fruit and vegetable intake recommendations [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In the rural Southeastern US, these geographic, income, and race/ethnicity groups often intersect and overlap, contributing to potentially greater risk of inadequate fruit and vegetable intake [17].…”
Section: Introductionmentioning
confidence: 99%